Experiences of Alaska Native people living with burn injury and opportunities for health system strengthening - Mallory B. Smith; Elisha Brownson; Andrea K. Newman; Christopher Madison; Molly Fuentes; Dagmar Amtmann; Gretchen J. Carrougher; Nicole S. Gibran; Barclay T. Stewart (BMC, 2023)
Abstract Background Injuries are a leading cause of death and disability for Alaska Native (AN) people. Alaska Native Tribal Health Consortium (ANTHC) is supporting the development of a burn care system that includes a partnership between Alaska Native Medical Center (ANMC) in Anchorage, AK and UW Medicine Regional Burn Center at Harborview Medical Center (HMC) in Seattle, WA. We aimed to better understand the experiences of AN people with burn injuries across the care continuum to aid development of culturally appropriate care regionalization. Methods We performed focus groups with twelve AN people with burn injury and their caregivers. A multidisciplinary team of burn care providers, qualitative research experts, AN care coordinator, and AN cultural liaison led focus groups to elicit experiences across the burn care continuum. Transcripts were analyzed using a phenomenological approach and inductive coding to understand how AN people and families navigated the medical and community systems for burn care and areas for improvement. Results Three themes were identified: 1-Challenges with local burn care in remote communities including limited first aid, triage, pain management, and wound care, as well as long-distance transport to definitive care; 2-Divergence between cultural values and medical practices that generated mistrust in the medical system, isolation from their support systems, and recovery goals that were not aligned with their needs; 3-Difficulty accessing emotional health support and a survivor community that could empower their resilience. Conclusion Participants reported modifiable barriers to culturally competent treatment for burn injuries among AN people. The findings can inform initiatives that leverage existing resources, including expansion of the Extension for Community Healthcare Outcomes (ECHO) telementoring program, promulgation of the Phoenix Society Survivors Offering Assistance in Recovery (SOAR) to AK, coordination of regionalized care to reduce time away from AK and provide more comfortable community reintegration, and define rehabilitation goals in terms that align with personal goals and subsistence lifestyle skills. Long-distance transport times are non-modifiable, but better pre-hospital care could be achieved by harnessing existing telehealth services and adapting principles of prolonged field care to allow for triage, initial care, and resuscitation in remote environments.